2020
DOI: 10.3389/fmed.2020.598903
|View full text |Cite
|
Sign up to set email alerts
|

Part II: Accuracy of Teledermatology in Skin Neoplasms

Abstract: Teledermatology has been proving to be of great help for delivering healthcare, especially now, during the SARS-CoV-2 pandemic. It is crucial to assess how accurate this method can be for evaluating different dermatoses. Such knowledge can contribute to the dermatologists' decision of whether to adhere to teledermatology or not. Our objective was to determine the accuracy of teledermatology in the 10 most frequent skin neoplasms in our population, comparing telediagnosis to histopathological report and in-pers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…[12][13][14] Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms. 15,16 High levels of satisfaction with teleservices has been reported previously in patients having acne. 17 In this study, 62% of acne patients reported being satisfied or very satisfied with teleconsultation services.…”
Section: Discussionmentioning
confidence: 83%
“…[12][13][14] Two retrospective studies from Brazil reported high degree of accuracy with teledermatology in inflammatory dermatoses and moderate accuracy for neoplasms. 15,16 High levels of satisfaction with teleservices has been reported previously in patients having acne. 17 In this study, 62% of acne patients reported being satisfied or very satisfied with teleconsultation services.…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies, overall diagnostic accuracy for malignancies varied between 51% and 87.3%, while concordance ranged from moderate to substantial agreement (κ = 0.41–0.63) [ 49 , 50 , 51 ]. We observed a diagnostic accuracy at the higher end by reaching 85.3%, while the diagnostic concordance was 0.644.…”
Section: Discussionmentioning
confidence: 99%
“…Skin cancer detection through telemedicine channels is in agreement with histopathology in about 70% of diagnoses by dermatologists (Giavina-Bianchi et al 2020 ) and 50% by primary care physicians (Bridges et al 2019 ). These moderate performance levels leave room to further improvements, possibly by artificial intelligence-enhanced methods.…”
Section: Discussionmentioning
confidence: 74%